Dimensionamento de uma rede de fibra óptica pon ftth - Meneses Filho, Esdras Antônio de (Universidade Federal Rural do Semi-Árido, 2018)
In the last years, there has been a considerable increase in internet consumption, mostly due to sharing / playback sites and video streaming at video resolutions in FULL HD, 2K or 4K. Therefore, the provision of plans with greater bandwidth became necessary for the consumer to be able to consume contents with high rates of data transfer. The use of fiber optical in internet access networks has revolutionized the way of consumption, since the rates of data transfer obtained from fiber optic are very superior to other technologies, such as internet distribution via coaxial cable and via radio. Other advantages include low signal loss, low network maintenance, increased safety, lower power consumption, lightness and non-flammable characteristics. For the design of an optical network it is necessary to have different knowledges, from the technology used in the equipment to the best way to use these equipment in the construction of the optical network. During the design of the network, it is necessary to define which type of optical network will be used. There are two types of fiber optic access networks: active optical (AON) and passive (PON) networks. Optical networks of the PON type are much more used because they require electrical power only at the ends of the network, source and consumer, reducing maintenance costs and future network problems. Another criterion that must be considered is the proximity of the optical fiber to the point of service. For an FTTH (Fiber-to-the-home) network, for example, the optical fiber goes to the client's home. In this work, we chose to design a PON FTTH fiber optic network. The design of a PON FTTH network has several phases, such as the choice of construction site, penetration rate, positioning of optical termination box (OTB) and optical distribution box (ODB), and the positioning of primary and secondary routes, for example. The average bandwidth consumption per residence was calculated. It was analyzed which type of multiple access technology has the best cost-benefit. In addition, the optical network was designed to have a power budget with a good margin of safety, preventing the network from having problems of attenuation or loss of signal.
Monografia
Keywords: Internet; Fibra óptica; PON; AON; FTTH; CTO; ENGENHARIAS::ENGENHARIA ELETRICA